Experimental evidence for mineral-controlled release of radiogenic Nd, Hf and Pb isotopes from granitic rocks during progressive chemical weathering - Dausmann, Veit; Gutjahr, Marcus; Frank, Martin; Kouzmanov, Kalin; Schaltegger, Urs (Chemical geology, 2019)
The role of accessory minerals in the incongruent release of Hf and Pb during continental weathering and its implications for the generation of distinct seawater isotope compositions is subject of debate. While it has been suggested that radiogenic Hf and Pb isotope signatures released during the dissolution of rocks are controlled by the relative abundances of minerals with distinct isotope compositions and differences in their resistance to dissolution there has not been a comprehensive experimental investigation of these processes to date. We carried out systematic sequential leaching experiments on fresh and partly weathered granitic rock samples as well as separated zircons from the Central Aar Granite in Switzerland. Combined with major and rare earth element concentrations our new quantitative experimental data reveal systematic preferential release of radiogenic Nd, Hf and Pb isotopes primarily controlled by dissolution characteristics of the host rock's easily dissolvable accessory and major minerals, in particular apatite and sphene, during weak chemical weathering. Moreover, Pb isotope signatures of incipient weathering conditions, contrary to expectations, indicate initial congruent release of Pb from freshly exposed mineral surfaces that becomes subsequently incongruent. During more advanced chemical weathering stages, as well as enhanced physical weathering conditions, the dissolution of major minerals (i.e. feldspars) becomes dominant for Nd and Pb isotope signatures, whereas Hf isotopes are still dominated by contributions from highly radiogenic accessories. Additional leaching experiments of zircon separates were performed to test the specific role of zircons for Hf isotope compositions of riverine runoff. It is demonstrated that zircon is more efficiently dissolved when physical weathering is enhanced. This increased Hf release originating from partial dissolution of zircons, however, is quantitatively not sufficient to explain less radiogenic Hf isotope signatures in seawater during episodes of enhanced mechanical erosion alone. Moreover, the observed addition of Hf from the more congruent dissolution of the zircon-free fractions of the parent rock due to enhanced physical weathering indicates that these minerals also play an important role in controlling Hf isotope signatures released under deglacial conditions.